Trade off between inflation and unemployment? The state as a direct employer - Osorio Vaccaro, Jorge G. (2019)
In this paper it will be raised, contrary to what is suggested by the predominant orthodoxy in economic science, that the welfare of society improves not only controlling inflation but also and possibly more importantly, reducing unemployment. As will be seen, the objectives of reducing unemployment through direct state intervention using activist demand policies, as suggested by the Post Keynesian approach, would not accelerate inflation. Consequently, it would not be true as suggested by the analysis derived from the Phillips Curve, that reducing unemployment would necessarily increase inflation and that for this to not happen a certain NAIRU goal must be set (an unemployment rate that does not accelerate inflation). The approach that will be presented, in line with what is suggested by the Poskeynesian School, argues that the state can assume the role of “employer of last resort labor”. In this way, the state could directly hire unemployed labor (openly or disguised as informality), which constitutes a serious problem for developing economies.